(untitled) (World Bulletin of Public Health, 2022)
Diarrhea is one of the deadly diseases in children. Diarrhea mortality rates are very important in the world, so they require serious treatment measures. ORS (Oral Rehydration Salt) can be considered as one of the effective drugs in the treatment of diarrhea. The level of mothers’ awareness about using ORS powder is also one of the predisposing factors for effective treatment of diarrhea.